2019
DOI: 10.3390/ani9060378
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Culture of Skin-Derived Differentiated and Stem-Like Cells Obtained from the Arabian Camel (Camelus dromedarius)

Abstract: Elite camels often suffer from massive injuries. Thus, there is a pivotal need for a cheap and readily available regenerative medicine source. We isolated novel stem-like cells from camel skin and investigated their multipotency and resistance against various stresses. Skin samples were isolated from ears of five camels. Fibroblasts, keratinocytes, and spheroid progenitors were extracted. After separation of different cell lines by trypsinization, all cell lines were exposed to heat shock. Then, fibroblasts an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…The current results represent a continuation of our experiments that were performed to compare the species differences in in vitro thermotolerance to elucidate species adaptability and acclimation to extreme heat exposure [16,17,24,34]. Recently, we showed that camel cells better tolerated chronic heat shock (45 • C for 20 h) than porcine cells [16], and the results of this study revealed that cow cells were more tolerant to acute heat shock than sheep cells on the primary and first passage level, as well as for cryopreserved fibroblasts.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The current results represent a continuation of our experiments that were performed to compare the species differences in in vitro thermotolerance to elucidate species adaptability and acclimation to extreme heat exposure [16,17,24,34]. Recently, we showed that camel cells better tolerated chronic heat shock (45 • C for 20 h) than porcine cells [16], and the results of this study revealed that cow cells were more tolerant to acute heat shock than sheep cells on the primary and first passage level, as well as for cryopreserved fibroblasts.…”
Section: Discussionmentioning
confidence: 68%
“…For instance, thermotolerance was found physiologically in certain species as a form of estivation [32,33]. It could vary among certain cells in the same species [17,34]. Cells show variability in thermotolerance, apoptosis, and necrosis depending on the cell culture method; the three-dimensional (3D) culture system shows increased survival plausibly by activating the protective processes related to enhanced HSP70 expression as compared with the two-dimensional (2D) culture system at 45 • C for 120 min [35].…”
Section: Introductionmentioning
confidence: 99%
“…In tissues derived from the domestic porcine, a species phylogenetically close to the collared peccaries, all the explants adhered within 3 days to 8 days (Silvestre, Sánchez & Gómez, 2004). The similarity among these data can be related to the culture medium because in a majority of these studies, DMEM containing FBS, antibiotic, and antimycotic solution was used (Magalhães et al, 2017;Saadeldin et al, 2019;Siengdee et al, 2018). Since primary culture needs to mimic the in vivo PeerJ reviewing PDF | (2019:11:43206:1:1:CHECK 7 Apr 2020)…”
Section: Discussionmentioning
confidence: 89%
“…The cell line can be considered as the first constituent of the peccary invitrome and a resource for future studies in many disciplines (Barioch 2018;Bols et al, 2017). Thus, the ear tissues of collared peccaries can be isolated and grown into fibroblasts in an adherent culture for Manuscript to be reviewed preserve valuable species, and as sources for biological research (León-Quinto et al, 2009;Mehrabani et al, 2014;Saadeldin et al, 2019;Siengdee et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Arabian camel skin fibroblast cell line (SACAS) was also used in the expression of small heat shock proteinbeta-1((HSPB-1) from in dromedary camel [38]. Recently, various differentiated cells have been isolated from the dromedary camel dermis including fibroblasts and keratinocytes, cyst-forming cells, as well as multipotent dermal stem cells [39]. Those stem cells are capable of forming spheres that form osteoblasts, neurons and adiposities.…”
Section: Stem Cellsmentioning
confidence: 99%